2006
DOI: 10.1166/jnn.2006.666
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)/Silica Nanocomposites: Morphology and Thermal Degradation Kinetics

Abstract: The morphology of self-assembled poly(vinyl alcohol)/silica (PVA/SiO2) nanocomposites is investigated with atomic force microscopy (AFM) and transmission electron microscopy (TEM). It is found that the SiO2 nanoparticles are homogenously distributed throughout the PVA matrix in a form of spherical nano-cluster. The average size of the SiO2 clusters is below 50 nm at the low contents (SiO2 < or =5 5 wt%), while particle aggregations are clearly observed and their average size markedly increases to 110 nm when 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 0 publications
6
19
0
Order By: Relevance
“…There are various silanol groups in the nanosilica that can change the crystalline behaviors of the polymeric matrix, increase hydrogen bonding effects, and affect the fluorescent properties of composite end products. Furthermore, thermal resistance is the most significant property of polymeric materials, as it controls their spectral stability, mechanical properties, shelf lives, and durability (Cho et al 2003;Jin et al 2003;Peng et al 2006;Peng and Kong 2007;Saat and Johan 2014). In this paper, the modification of the properties of PVA by the incorporation of highly reactive nanocellulose, isolated from oil palm empty fruit bunches (OPEFB), and nanosilica were studied.…”
Section: Introductionmentioning
confidence: 99%
“…There are various silanol groups in the nanosilica that can change the crystalline behaviors of the polymeric matrix, increase hydrogen bonding effects, and affect the fluorescent properties of composite end products. Furthermore, thermal resistance is the most significant property of polymeric materials, as it controls their spectral stability, mechanical properties, shelf lives, and durability (Cho et al 2003;Jin et al 2003;Peng et al 2006;Peng and Kong 2007;Saat and Johan 2014). In this paper, the modification of the properties of PVA by the incorporation of highly reactive nanocellulose, isolated from oil palm empty fruit bunches (OPEFB), and nanosilica were studied.…”
Section: Introductionmentioning
confidence: 99%
“…13 Thermal stability is one of the most crucial properties for polymeric material, as it ultimately governs the mechanical properties, durability, spectral stability, shelf life, and life cycle of the polymers. [14][15][16][17] Once the degradation begins, the abovementioned properties gradually deteriorate. However, the incorporation of inorganic NPs in polymers results in somewhat improved thermal resistance of the host polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These NPs have been used by other researchers individually in different wt% in order to modify epoxy coating system in terms of thermal, mechanical, and corrosion properties. 6,10,11,16 However the focus of the current study is to have a comparative analysis of the effect of these NPs on thermal, mechanical, and morphological properties of the cured coatings. The addition of different types of filler into poly acrylic coating revealed that a small percentage of nanoalumina particles markedly improve the scratch and hardness properties of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-linking reaction of PVA with GLA resulted in the formation of acetal groups and ether linkages which decreased the swelling behaviour of the PVA (Mansur et al 2008). Meanwhile, SiO 2 was added to the BEN-PVAG composite as a filler to increase its mechanical resistance (Peng et al 2006) and APS was applied as an oxidant to initiate the polymerization of hydrogen on the PVA chain . Meanwhile, the P-25TiO 2 composite top layer was prepared exactly according to the procedures reported by Nawi and Zain (2012).…”
Section: Resultsmentioning
confidence: 99%